Religious identity in the Christian religion in the sources of religious teachings and sanctities, worship, feasts and holy days (Islamic Sciences Journal, 2023)
This research deals with the Christian religion, what are its most important features, and the places where the Christian identity is defined. It has three topics: I explained in the first topic: the definition of the Christian religion, and its most prominent prophets, and there are two requirements: the first requirement: the definition of the Christian religion in language and terminology: and the second requirement: the most prominent prophets of religion The Christian: Then, in the second topic, I showed: the characteristics of the Christian religion, doctrinal, legal, and ethical, and it contains four demands: The first requirement: religious identity in the sources of teachings of the Christian religion: The second requirement: religious identity in Christian sanctities, and the third requirement: the religious gap in worship and practical rulings Christianity and the fourth requirement: Christian religious identity in holidays and holy days.
Keywords: religious sanctities, Christian religion, Religious identity